Gender congruence and entrepreneurial investments: the role of others’ reactions - Wieland, Alice (International Journal of Gender and Entrepreneurship, 2025)
The purpose of this research is to explore the decision processes that underlie the gender gap in entrepreneurial investments. The present research explores how gender congruence with a sex-typed business opportunity influences anticipated reactions from others who may provide or withhold support and resources, how these affect the assessed probability of venture success and the amount the entrepreneur is willing to invest (WTI) in the opportunity.,A theoretical model is presented and empirically tested via path analysis. A pilot and an experimental study model explore how gender congruence influences entrepreneurial investment decisions. The experimental study uses a repeated measures design examining the experimental effects two sex-typed business opportunities crossed with participant gender (gender congruence) on anticipated others’ reactions, assessed probability of venture success and investment amount (WTI).,Gender congruence of a business opportunity influences anticipated others’ reactions, whether they will be supportive or not, of pursuing the opportunity. This in turn influences the estimated probability of success of the venture and the amount the prospective entrepreneur is willing to invest in it. These socio-cognitive decision processes reinforce the gender gap in entrepreneurship since participants anticipate less access to others’ support for gender incongruent opportunities. Although the mediational model indicates most proposed relationships and paths are invariant across genders, the exception was that women did not report higher WTI for the gender congruent venture.,The research applies the latest thinking in social psychology on gender norm violations to entrepreneurship, measuring how anticipated reactions from others are a factor in predicting estimates of venture success probability and self-investments.
Keywords: dept.mgt; peer-reviewed

The interplay of power, incentives, academic freedom, and gender equity - Wieland, Alice; Jansen, Amy (Journal of Academic Freedom, 2024)
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.
Keywords: dept.lib; dept.mgt

Developing resilient leaders: a training for students - Jansen, Amy L.; Wieland, Alice (Journal of Leadership Education, 2024)
This assignment is designed to enhance resilience among students in leadership courses. It leverages the US Army’s Master Resilience Training (MRT) framework and positive psychology to develop resiliency skills.A three-part experiential workshop integrates academic readings (providing a foundation of resilience concepts), explores the influence of personal identities on leadership and connects leadership skills with resilience concepts.Participants reflect on self-awareness tools and positive psychology and create personalized action plans. Participants' resilience skills are enhanced with their personalized resiliency plan.The program provides a structured approach to resilience training, which can be integrated into university curriculums. Students gain self-awareness and psychological tools to manage challenges, which are valuable for personal growth and professional development. There is a persistent gender gap in leadership, and for women to attain greater parity in leadership positions, resilience skills are imperative. By focusing on identity-related factors, the program prepares future leaders for challenges in attaining leadership positions.This program is uniquely tailored for students aspiring to leadership positions, with an emphasis on the role of identity, such as gender, in leader emergence and overcoming related challenges.
Keywords: dept.lib; peer-reviewed

Boosting Performance on an Evaluative Math Test: Goal Activation vs Self-Affirmation - Wieland, Alice M.; Burnham, Thomas A. (Psychological Reports, 2016)
This study compared the effectiveness of goal activation versus self-affirmation and a control condition as interventions for increasing performance on an evaluative task (a difficult math test; N = 78; M age = 20.3 yr., SD = 1.9). Although there has been much recent literature on the effects of activating goals, the existing literature does not examine possible spillover effects of activating goals on performance tasks. Results indicated that goal activation resulted in significant performance enhancements over both the self-affirmation and control conditions, while self-affirmation did not improve performance significantly relative to the control condition. Additionally, interest in the task, as a cue for self-regulatory resources, mediated the effect of goal activation on increased performance.
Keywords: dept.mgt

Designing Entrepreneurship Experiments: A Review, Typology, and Research Agenda - Hsu, Dan K.; Simmons, Sharon A.; Wieland, Alice M. (Organizational Research Methods, 2017)
This article discusses the current and potential application of experimental methods to the study of entrepreneurship phenomena. Drawing on a review of experimental studies in entrepreneurship research, we discuss the advantages and disadvantages of experimental research designs for entrepreneurship research as a primer for those interested but not overly familiar with these methods. To advance research agendas and theory in the field, we introduce a typology of experimental manipulations that highlight alternative design choices based on the nature of their participant impact and realism of context. Finally, we provide an overview of areas of opportunity within the entrepreneurship literature for application of methods best suited to provide greater insight into the causal mechanisms at play.
Keywords: dept.mgt; peer-reviewed

Gender differences in the endowment effect: Women pay less, but won’t accept less - Wieland, Alice; Sundali, James; Kemmelmeier, Markus; Sarin, Rakesh (Judgment and Decision Making, 2014)
We explore different contexts and mechanisms that might promote or alleviate the gender effect in risk aversion. Our main result is that we do not find gender differences in risk aversion when the choice is framed as a willingness-to-accept (WTA) task. When the choice is framed as a willingness-to-pay (WTP) task, men are willing to pay more and thus exhibit lower risk aversion. However, when the choice is framed as a willingness to accept task, women will not accept less than men. These findings imply gender differences in the endowment effect. We also find that the effect size of the gender difference in risk aversion is reduced or eliminated as the context changes from tasks framed as gambles to other domains; and that attitudes toward gambling mediate the gender effect in gambling framed tasks.
Keywords: dept.mgt; endowment effect; gambling attitudes; gender; peer-reviewed; risk attitudes; risk aversion; sex differences